Advanced manufacturing techniques for engineering and engineered materials - Thanigaivelan, Rajasekaran, 1977-; Rajan, N., 1977-; Arul, T. G., 1976- (Advances in chemical and materials engineering (ACME) book series., 2022)
"This book highlights the latest trends in manufacturing processes such as 3D Printing, Casting, Welding, Surface Modification, CNC, Non- Traditional, Industry 4.0 Ergonomics and Hybrid Machining Methods"--